KONSEP, PARADIGMA DAN IMPLIKASINYA TERHADAP PEMBANGUNAN PENDIDIKAN DI INDONESIA - Suwardi Suwardi; Slamet Riyadi; Nuradilah Nuradilah (Ensiklopedia Education Review, 2022)
This research explains, it is necessary to make innovative-creative thinking regarding an integrated education system development model, which can mix and accommodate efforts to improve and achieve various educational policies (equitable and expanding access to education, improving the quality of education, relevance of education, etc.) targeted) together, not partially and sequentially, including its sustainability aspects. The results of increasing and achieving equity and expanding access to education, need to be accompanied by improving the quality of education (with a massive quality improvement model, for example), but also need to pay attention to aspects of relevance (by, for example, matching the curriculum with existing empirical, by updating the syllabus every year once, even without changing the formal curriculum). The sustainability aspect also needs to be considered, so that the implementation of a policy does not only depend on whether there is a subsidy from the center, while when subsidies are eliminated or revoked, for example, then it does not work. Furthermore, the success of education is also inseparable from aspects of leadership (leadership). So that in this case the selected policy makers should be those who side with education and not those who do not have a vision for the world of education. Choosing officials or leaders with character and justice is one of the efforts to improve people's political education.Keywords: Concept, Paradigm, Implications, Educational Development.